2007
DOI: 10.2174/1874839200701010001
|View full text |Cite
|
Sign up to set email alerts
|

Practical Considerations for the Reintroduction of Large, Terrestrial,Mammalian Predators Based on Reintroductions to South Africa's Eastern Cape Province

Abstract: Abstract:The expansion of conservation estate in South Africa has seen large predators increasingly reintroduced in order to restore ecological integrity, conserve threatened species and maximise tourism. Reintroductions occurred at fenced, ecotourism sites in South Africa's Eastern Cape Province. Lion Panthera leo reintroduction began in 2000 and has been highly successful with a population of 56 currently extant in the region arising from 35 reintroduced individuals. The African wild dog Lycaon pictus popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 46 publications
0
65
0
Order By: Relevance
“…The leopard showed similar movement and home range patterns to wild conspecifics, with a large home range characteristic of more arid areas (Marker & Dickman 2005;Hayward et al 2007a;Weilenmann et al 2010) with low densities of prey ), including the initial roaming behaviour typical for translocated carnivores (Somers & Gusset 2009). …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The leopard showed similar movement and home range patterns to wild conspecifics, with a large home range characteristic of more arid areas (Marker & Dickman 2005;Hayward et al 2007a;Weilenmann et al 2010) with low densities of prey ), including the initial roaming behaviour typical for translocated carnivores (Somers & Gusset 2009). …”
Section: Discussionmentioning
confidence: 90%
“…), most have been unsuccessful due to human-induced mortality. The ranging behaviour that exposed the cheetahs to fatal contact with people could be restricted by predator-proof perimeter fencing (Hayward et al 2007a;Gusset et al 2008;Marnewick et al 2009), but this also limits the natural exchange of animals among sites ). Pre-release aversive conditioning (Griffin et al 2000) and total separation from humans while in the holding facility during feeding and cleaning times, and using large protected areas as release sites such as with the leopard in this study, might thus be indicated in future cheetah rehabilitation attempts.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent decades lions have been reintroduced into over 40 small (<1000 km 2 ), fenced areas, including private reserves, conservancies, protected areas, national and provincial parks, hereafter referred to as 'reserves' (reviewed by Funston 2008;Slotow & Hunter 2009). These lion reintroductions have been successful on the individual reserve level; however, the introduced lions are all intensively managed (Hayward et al 2007a;Hunter et al 2007) and increasingly genetically compromised (Trinkel et al 2008(Trinkel et al , 2010, the net effect of which reduces their conservation value on a regional scale (Slotow & Hunter 2009). It has been suggested that small reserves in South Africa need to move away from intensive management in isolation towards a managed metapopulation approach (Funston 2008;Slotow & Hunter 2009;Hayward & Kerley 2009;Trinkel et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Managers were asked to state which (if any) large predator species (cheetah, lion, spotted hyaena, wild dog) had been reintroduced onto the PLCA. Leopard (Panthera pardus) were excluded from this list because they are not constrained by fences, have vast home ranges that span multiple properties, and their secretive nature means that they are rarely seen by tourists (Hayward et al 2007a, Fattebert et al 2015. Spotted hyaena occurred on one PLCA, and wild dog did not occur on any PLCAs (see Results); therefore, they were excluded from further analyses.…”
Section: Sample Selectionmentioning
confidence: 99%